CURRICULUM OF MULTICULTURAL EDUCATION IN LOCAL HISTORY - AULIA NOVEMY DHITA SURBAKTI (Sriwijaya University Learning and Education International Conference, 2016)
Curriculum is one of tool to achieve the goal of education for a nation that isupdated according to the needs and social conditions the country and in line withdevelopments in science and technology. Curriculum must always be able toanticipate the conditions for a dynamic society. Multiculturalism is one issue thatshould be concern in education since Indonesia is a multiclktural country completewith multicultural problems. Education is a strategic container to stem themulticultural issue. Multicultural education is not onlu education about cukturaldiversity but also provide space on education to change perspectives essentialmonoculture, prejudiced and discriminatory to multiculturalist perspective thatvalue diversity and differences, tolerant and good attitude. In conjuction withteaching history, multicultural education curriculum can be integrated with localhistory. Multicultural education curriculum in local history study provides anopportunity for local history cultural diversity and understanding of the past be areflection of the settlement terms of preventif basic and multicultural issue at thistime.